Carbon dioxide emissions from lakes and reservoirs of China: A regional estimate based on the calculated pCO2. (December 2017) - Wen, Zhidan; Song, Kaishan; Shang, Yingxin; Fang, Chong; Li, Lin; Lv, Lili; Lv, Xianguo; Chen, Lijiang
Abstract: The role of inland water in CO2 exchange with the atmosphere was evaluated on the basis of calculated partial pressure of CO2 ( p CO2 ) from sampling of 207 lakes and 84 reservoirs across China in late summer. The results suggested that almost 60% of these water bodies were supersaturated with CO2 with respect to atmosphere, and the collected reservoirs samples exhibited higher mean p CO2 than lakes. The mean p CO2 in fresh water lakes was about 3.5 times of the value in saline lakes. The lakes and reservoirs were divided into five groups (Inner Mongolia -Xinjiang plateau region, Tibetan Plateau region, Northeastern plain and mountainous region, Yunnan- Guizhou Plateau region, and Eastern plain region). The Yunnan- Guizhou Plateau region showed the highest p CO2 compared with other regions, most likely due to the typical karst landforms, karst processes may promote aqueous CO2 concentration, and karstification has a significant effect on the capture of atmospheric CO2 . Inner Mongolia-Xinjiang plateau and Tibetan Plateau region reserviors showed negative CO2 flux to atmosphere, other waters in this study all supersaturated with CO2 with respect to the atmosphere. A which We analyzed the relationship between p CO2 and environmental variables, and results showed that some indicators had correlations with p CO2 in individual region such as total phosphorus, dissolved organic matter, and total suspended solids, but the relationship could not be observed with all surveyed waters. This indicated that it might be much more effective in a smaller regional scale than the broadened scale when the environmental factors were used as the predictor of p CO2 in lakes. Therefore, the common algorithm that extrapolates CO2 concentration or emission flux from the study region to a wider scale might not be accurate because of the changes in the environmental and water quality conditions. Highlights: 60% of 207 lakes and 84 reservoirs across China were supersaturated with CO2 . The surveyed reservoirs exhibited higher mean p CO2 than lakes in China. The mean p CO2 in fresh water lakes was about 3.5 times of in saline lakes. Yunnan- Guizhou Plateau showed the highest water p CO2 compared with other regions. Environmental factor as the predictor of p CO2 is just effective in small region.